Simulation of the Atomic Structure and Distribution of Vacancies in the Ionic Conductor LaxCe1/2 – xLixTiO3 - S.A. Kalkuta (Журнал нано- та електронної фізики)
The atomic and electronic structure of the ion conductor La0.25Ce0.25Li0.25TiO3 with ab-initio method FLAPW-GGA was studied. The pair interaction potentials of lithium ions were obtained. Dependences of the concentration of vacancies on the concentration of lithium ions at different temperatures in the compounds LaxCe0.5 – xLixTiO3 and La(2 – x)/3LixTiO3 were obtained by the Monte-Carlo method. It is shown that the amount of lithium vacancies participating in the conductivity is significantly higher in the compound La0.25Ce0.25Li0.25TiO3.